Experimental Study of Conduction Heat Transfer Using Paraffin Phase Change Material on Bricks - Fahrezi, Dian; Irawan, Doddy; Iwan, Muhammad; Julianto, Eko; Fahrurrozi Fahrurrozi; Govari, Muhammad Khoirul (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
This research examines the effect of bricks enhancement with phase change material (PCM) consisting of paraffin on their thermal considerations. The experimental methods were aimed at investigating the mechanisms of temperature transfer throughout the thermal rounds, mimicking diurnal fluctuations of temperature. Due to the high amount of latent heat contained in paraffin a portion of it was transferred into regular bricks with temperature probes tracing the heat processes. It is shown that enhancement of bricks with PCM reduced temperature range and controlled the rate of heat transmission more than the ordinary bricks did. It was significant that the PCM-embedded bricks did not drift in heat and were able to stock up excess heat during the day and release it at night which resulted in monumental energy efficiency and comfort in thermal standing. The conversation additionally seeks to bring out the function of paraffin in insulation which does not only save energy consumption but goes forward to maintain comfortable temperatures within the building. The study finally achieved its goal and assert that energy saving with the use of PCM enhanced bricks in construction makes it a preferable material in regards to energy and the fight against climate change.